2016
DOI: 10.1111/jam.13069
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antiviral activity of Lactobacillus casei and Bifidobacterium adolescentis against rotavirus infection monitored by NSP 4 protein production

Abstract: Aims: The aim of this study was to determine the antiviral activity of four probiotic metabolites (Lactobacillus and Bifidobacetrium species) against rotavirus in vitro infection monitored by the NSP4 protein production and Ca 2+ release. Methods and Results: The antiviral effect of the metabolites was performed due a comparison between a blocking model and an intracelullar model on MA104 cells, with the response of NSP4 production and Ca 2+ liberation measured by flow cytometry. Significant results were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 52 publications
2
39
0
1
Order By: Relevance
“…The activity of probiotics and prebiotics against RV pathogenesis may be attributable to decreased viral shedding possibly due to the interaction of probiotics (or their metabolites) and prebiotics with the viral particles avoiding the entry into enterocytes and as a consequence reducing the RV replication (Rigo-Adrover et al 2017 ). Moreover, the in vitro effect of metabolites of Lactobacillus casei , and Bifidobacterium adolescentis was associated with a reduced expression of the RV enterotoxin NSP4 and reduced levels of Ca 2+ liberation suggesting that cell will not reach the electrolyte imbalance caused by this pathway (Olaya Galán et al 2016 ). On the other hand, the modulation of RV immune response by probiotics and prebiotics has been associated with a generalized antiviral response via pattern recognition receptor signaling and through promoting type I IFNs, which are key regulators of IFN signaling pathway (Ishizuka et al 2016 ; Kang et al 2015 ).…”
Section: Probiotics and Prebiotics Vs Rotavirus Gastroenteritismentioning
confidence: 99%
“…The activity of probiotics and prebiotics against RV pathogenesis may be attributable to decreased viral shedding possibly due to the interaction of probiotics (or their metabolites) and prebiotics with the viral particles avoiding the entry into enterocytes and as a consequence reducing the RV replication (Rigo-Adrover et al 2017 ). Moreover, the in vitro effect of metabolites of Lactobacillus casei , and Bifidobacterium adolescentis was associated with a reduced expression of the RV enterotoxin NSP4 and reduced levels of Ca 2+ liberation suggesting that cell will not reach the electrolyte imbalance caused by this pathway (Olaya Galán et al 2016 ). On the other hand, the modulation of RV immune response by probiotics and prebiotics has been associated with a generalized antiviral response via pattern recognition receptor signaling and through promoting type I IFNs, which are key regulators of IFN signaling pathway (Ishizuka et al 2016 ; Kang et al 2015 ).…”
Section: Probiotics and Prebiotics Vs Rotavirus Gastroenteritismentioning
confidence: 99%
“…However, before moving to clinical trials, the safety and efficacy of probiotics need to be proven in preclinical models. In this sense, preclinical evidence has been accumulated for the following species: Lactobacillus casei [32][33][34], Lactobacillus plantarum [31], Lactobacillus rhamnosus GG [5,14,26,35], Bifidobacterium adolescentis [34], Bifidobacterium bifidum [29], Bifidobacterium infantis [29], Bifidobacterium breve [13,36], and Bifidobacterium lactis [35]. In addition, these previous studies led to the further study of the clinical evidence for the following species: Lactobacillus acidophilus [16,20,32,37], L. casei [26], Lactobacillus reuteri [38,39], L. rhamnosus GG [16,17,20,22,[40][41][42][43], Lactobacillus sporogenes [44,45], B. lactis [46][47][48], and Bifidobacterium longum [16,20,37].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated the beneficial effect of probiotics against rotavirus infection [ 9 , 10 ]. Most of them are clinical assays proving that the use of probiotics can lessen severity and duration of rotavirus diarrhea [ 11 ], whereas other studies are performed in vitro directed to the understanding of molecular and biochemical pathways associated with the mechanism employed by probiotics to accomplish the antiviral activity [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%